"I Don't Know How, But I'll Figure It Out Somehow": Future Possible Selves and Aspirations in "At-Risk" Early Adolescents. (February 2018) - Wainwright, Lucy; Nee, Claire; Vrij, Aldert
Fostering positive future selves in mid-adolescence has shown promising results in reducing problematic behaviour, though little work has been done outside the United States or with younger children. We explored the link between future selves and delinquency in a younger sample of boys ( M age = 12, SD = 0.73, N = 126) in the United Kingdom, at the nascent stage of self-identity and anti-social behaviour. Participants, who varied in degree of self-reported delinquency and risk, described their short- and long-term possible selves and strategies to achieve them. Unlike findings for older samples (14+), we found no association between delinquency and future selves. Exposure to criminogenic risk revealed some differences regarding the nature of future selves. Those with delinquency and higher risk had fewer strategies for reaching goals. Findings are discussed in relation to self-identity theory and the timing and nature of interventions for children of this age.